Measuring the Effectiveness of Service Delivery : Delivery of Government Provided Goods and Services in India - Demirguc-Kunt, Asli; Klapper, Leora; Prasad, Neeraj (World Bank, Washington, DC, 2017)
This paper uses new survey data to measure the government's capacity to deliver goods and services in a manner that includes: high coverage of the population; equal access; and high quality of service delivery. The paper finds variation in these indicators across and within Indian states. Overall: (i) access to government provided goods and services is low -- about 60 percent of the surveyed population are unable to apply for goods and services they self-report needing; (ii) inequality in access is high -- women and poor adults are more likely to report an inability to apply for goods and services they need; and (iii) less than a third of the respondents who did manage to apply for a government delivered good or service found the application process to be easy. Access can be improved by reducing application costs and processing times, simplifying the application process, and providing alternative channels to receive applications.